Increase of leishmanicidal and tubercular activities using steroids linked to aminoquinoline - Antinarelli, Luciana Maria Ribeiro; Carmo, Arturene Maria Lima; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fukimura; Silva, Adilson Davida da; Coimbra, Elaine Soares; Salunke, Deepak B. (My University, 2012)
Background: Aminoquinoline/steroid conjugates were synthesized based on the fact that steroid transporters have been shown to accept and carry a variety of drugs. So, in continuing our research of antileishmanial and antitubercular drugs, aminoquinoline/steroid conjugates (12, 13, and 14) were regioselectively synthesized via 1, 3-dipolar cycloaddition of alkynes 3, 5, and 7 with azide 12. The aminoquinoline/steroids conjugates were evaluated in vitro against Leishmania major and Mycobacterium tuberculosis. Results: Regioselective synthesis of the novel aminoquinoline/steroid conjugates was achieved in very high yield. All aminoquinoline/steroid conjugates (12, 13, and 14) exhibited best results against Leishmania and M. tuberculosis than the respective alkyne intermediate structures (3, 5, and 7, respectively). Among them, the compound 12 exhibited the best activity for M. tuberculosis (MIC = 8.8 μM). This result is comparable to drugs commonly used in tuberculosis treatment. Also, for antileishmanial assay, the aminoquinoline/steroid conjugates demonstrated a significant activity against promastigote and amastigote forms of L. major. Conclusions: Addition of a steroid group to aminoquinoline molecules enhanced the leishmanicidal and antitubercular activities. These results highlight the importance of steroids as carrier.
Keywords: Antileishmanial drugs; Antituberculosis drugs; Click chemistry; Quinoline; Steroid